Kesejahteraan Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada CV Sugih Wangi Kecamatan Lemahsugih Kabupaten Majalengka - Pupung Pamungkas; Nining Kurniasih; Deni Istiono (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
This research was conducted to analyze the effect of workplace well-being and motivation on employee performance at CV Sugih Wangi in Majalengka Regency. The study employed a quantitative approach with a descriptive-verificative method. The population consisted of all 53 employees, who were also used as the sample through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through classical assumption tests, multiple linear regression, and hypothesis testing using t-tests and F-tests. The results indicate that workplace well-being has a positive and significant impact on employee performance. Motivation also shows a positive and significant effect on performance. Simultaneously, both variables—workplace well-being and motivation—significantly influence employee performance. These findings emphasize the importance for companies to create a conducive work environment and enhance employee motivation to achieve optimal performance